Multicriteria analysis of primary steelmaking technologies. (20th January 2016) - Weigel, Max; Fischedick, Manfred; Marzinkowski, Joachim; Winzer, Petra
Abstract: The climate impact of the iron and steel industry can be mitigated through increased energy efficiency, emission efficiency, material efficiency, and product use efficiency resulting in reduced product demand. For achieving ambitious greenhouse gas (GHG) mitigation targets in this sector all measures could become necessary. The current paper focuses on one of those four key measures: emission efficiency via innovative primary steelmaking technologies. After analysing their techno-economical potential until 2100 in part A of this publication, the current research broadens the evaluation scope for the crucial year 2050, based on a Multicriteria-Analysis (MCA). 12 criteria from five different categories ("technology", "society and politics", "economy", "safety and vulnerability" and "ecology") are used to assess the same four future steelmaking technologies in a systematic and holistic way in Germany, as one possible location. The technologies in focus are the blast furnace route (BF–BOF), blast furnace with carbon capture and storage (BF–CCS), hydrogen direct reduction (H–DR), and iron ore electrolysis (EW). These four technologies have been selected, as explained in part A of this paper, because they are the most commonly discussed technological options under discussion by policymakers and the iron and steel industry. The results of the current work should provide decision makers in industry and government with a long-term guidance on technological choices. In 2050 the MCA shows significantly higher preference scores for the two innovative routes H–DR and EW compared to the blast furnace based routes. The main reasons being higher scores in the economical and environmental criteria. BF–CCS shows its greatest weakness in the social acceptance and the safety and vulnerability criteria. BF–BOF has the lowest economy and ecology score of all assessed routes, which is due to the projected high cost for carbon dioxide emission and increasing prices for fossil fuels. A first indicative trend assessment from today towards 2050 shows that H–DR is the preferred MCA option from today on. Three exemplary weighting distributions (representing the perspectives of the steel industry, environmental organisations and the government), used to simulate different stakeholder angle of view, don't have a strong influence on the overall evaluation of the steelmaking routes. The results remain very similar, with the highest scores for the innovative routes (H–DR and EW). This leads to the conclusion that EW and in particular H–DR can be identified as the preferred future steelmaking technology across different perspectives. Specific innovation efforts and dedicated programs are necessary to minimize the time until marketability and to share the development burden. The similarity of the MCA results from different perspectives indicates a great opportunity to reach a political consensus and to work together towards a common future goal. Regarding the pressing time horizon a concentrated engagement for one (or few) technological choices would be highly recommended. Highlights: Integral assessment of four primary steelmaking routes conducted. Hydrogen direct reduction with highest preference across categories. Assessment results are robust against different perspectives. In practice, initiatives to expedite technological maturity are most important.